2009
DOI: 10.1159/000239685
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Response to Reward in Smokers and Cannabis Users

Abstract: Background: Cannabis is one of the most commonly used illicit drugs. Reduced neural and behavioral reactions to reward have been demonstrated in other forms of addiction, as expressed by reduced mood reactivity and lack of striatal activation to rewards, but this effect has not yet been investigated in cannabis users. Methods: We hypothesized that cannabis users and tobacco smokers would evidence lower positive mood ratings in rewarded conditions than control participants and that this reduction would be great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 99 publications
4
23
0
1
Order By: Relevance
“…Functional imaging revealed that while users did not differ behaviourally from non-users during the initial strategy stage, they displayed reduced activity in the anterior cingulate and medial prefrontal cortices in response to losses (Wesley et al, 2011). Strikingly, neural responses to early IGT losses predicted future improvements in task performance in controls, but not cannabis users, suggesting that impaired decision-making may arise from an insensitivity to losses, consistent with reports that regular and heavy cannabis users show abnormalities in affective and reward processing (Gruber et al, 2009; Martin-Soelch et al, 2009; Nestor et al, 2010). Indeed, computational modelling of IGT performance in cannabis users reveals that these individuals tend to be under-influenced by loss magnitude, treating each loss as a constant and minor negative outcome regardless of the size of the loss (Fridberg et al, 2010; but see Bishara et al, 2009).…”
Section: Cannabinoid Modulation Of Prefrontal Cortical Function: Fsupporting
confidence: 83%
“…Functional imaging revealed that while users did not differ behaviourally from non-users during the initial strategy stage, they displayed reduced activity in the anterior cingulate and medial prefrontal cortices in response to losses (Wesley et al, 2011). Strikingly, neural responses to early IGT losses predicted future improvements in task performance in controls, but not cannabis users, suggesting that impaired decision-making may arise from an insensitivity to losses, consistent with reports that regular and heavy cannabis users show abnormalities in affective and reward processing (Gruber et al, 2009; Martin-Soelch et al, 2009; Nestor et al, 2010). Indeed, computational modelling of IGT performance in cannabis users reveals that these individuals tend to be under-influenced by loss magnitude, treating each loss as a constant and minor negative outcome regardless of the size of the loss (Fridberg et al, 2010; but see Bishara et al, 2009).…”
Section: Cannabinoid Modulation Of Prefrontal Cortical Function: Fsupporting
confidence: 83%
“…This may also reflect more general deficits in performance monitoring, as increases have also been observed under conditions where errors are likely to occur (Carter et al, 1998) and during violations of outcome expectancy (Oliveira et al, 2007). These reductions may reflect decreased motivation as a result of experiencing monetary losses (Martin-Soelch et al, 2009; Simoes-Franklin et al, 2009). Differences in motivation did not appear to be a significant contributing factor in the study, however, as all individuals completed the task, and groups did not differ in the number of omitted or “no response” events on the task.…”
Section: Discussionmentioning
confidence: 99%
“…A separate line of research has suggested that cannabis use may adversely impact reward systems or drug-related cue salience. For example, a study examining the effect of a reward task on mood in adult cannabis users and non-users found that monetary reward had a positive impact on mood in non-users participating in a spatial recognition task, but had no such effect in cannabis users (Martin-Soelch et al, 2009). Moreover, the prefrontal–accumbens circuit is normally involved in reward processing related to goal-directed behavior and cellular adaptations resulting from repeated drug exposure are thought to critically modify this circuit so that it becomes biased toward drug seeking (Kalivas and Volkow, 2005).…”
Section: Discussionmentioning
confidence: 99%